2011
DOI: 10.1007/s00228-011-1149-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased major bleeding risk in patients with kidney dysfunction receiving enoxaparin: a meta-analysis

Abstract: Only patients with a GFR > 60 ml/min can be safely treated with enoxaparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 31 publications
1
28
0
5
Order By: Relevance
“…One small rct comparing tinzaparin and dalteparin found that both drugs accumulated in hemodialysis patients at therapeutic doses 41 . Similarly, a meta-analysis found an increase in bleeding risk with enoxaparin in patients with renal impairment 40 . Compared with longer-course treatment, short-course therapeutic doses (up to 5 days) of dalteparin or tinzaparin are less likely to be associated with bioaccumulation and might be reasonable for initiating oral anticoagulation with warfarin therapy.…”
Section: Moderate-to-severe Renal Impairmentmentioning
confidence: 94%
See 1 more Smart Citation
“…One small rct comparing tinzaparin and dalteparin found that both drugs accumulated in hemodialysis patients at therapeutic doses 41 . Similarly, a meta-analysis found an increase in bleeding risk with enoxaparin in patients with renal impairment 40 . Compared with longer-course treatment, short-course therapeutic doses (up to 5 days) of dalteparin or tinzaparin are less likely to be associated with bioaccumulation and might be reasonable for initiating oral anticoagulation with warfarin therapy.…”
Section: Moderate-to-severe Renal Impairmentmentioning
confidence: 94%
“…One large rct 36 and two smaller cohort studies 37,38 concluded that dalteparin at prophylactic doses was unlikely to contribute to bleeding in patients with renal impairment. Enoxaparin at prophylactic doses might bioaccumulate in patients with severe renal dysfunction, and dose reduction is recommended 39,40 .…”
Section: Moderate-to-severe Renal Impairmentmentioning
confidence: 99%
“…The included trials compared enoxaparin (typically 1 mg/kg every 12 hours) with ufh, fondaparinux, or tinzaparin, and treatment was given for a total of 1.5-10 days. The data revealed a significant increase in major bleeding with enoxaparin compared with the other anticoagulants (relative risk: 1.67; 95% ci: 1.12 to 2.50; p = 0.01); notably, however, the criteria used to measure major bleeding complications varied widely 31 . None of the available data are cancer-specific.…”
Section: Patients With Renal Insufficiencymentioning
confidence: 97%
“…The review concluded that warfarin should not be used in patients with advancing progressive disease 28 . The prothrombotic tendency of patients with advanced cancer suggests a need for indefinite treatment [28][29][30][31] . Currently, randomized clinical data support the use of lmwh treatment for 3-6 months 11,12 is often given for 6 months.…”
Section: Advanced Cancer and Duration Of Therapymentioning
confidence: 99%
“…In addition, it is indicated that ICH risk will rise with the increasing of drug dosage, age and degree of kidney damage. And a meta-analysis research found that when the low molecular heparin was used in patients with glomerular filtration rate <60 mL/minalthough the dose has been adjusted, the relative risk of bleeding is still as high as 1.67 [18].…”
Section: Parenteral Anticoagulants Related Cerebral Hemorrhage Commonmentioning
confidence: 99%